Development of PPKn Module for the Love of the Environment Material Using Example Non Example Learning Model to Increase Student Learning Activities in Class II Public Elementary School 040446 Kabanjahe T.P. 2018/2019 - Sari Jusnita Br Ginting; Dede Ruslan; Arif Rahman (BIRCU, 2020)
This study produced a PPKn module on environmental love by using the example non example learning model to increase student learning activities. The research method used is the Research and Development method which refers to the development of Borg and Gall (in Tegeh et al, 2014: 7-13). The module development process is carried out with three stages, namely the preliminary study stage, initial product development and product trials. The results of the study show that the assessment of eligibility by material experts obtained an average of 91.6%, the feasibility assessment by linguists obtained an average of 92, 1%, Feasibility assessment by design experts obtained an average of 80%. Individual trials with an average of 80.5% in the good category, small group trials with an average of 85.4% in the excellent category, and limited field trials with an average of 88.4% in the very good category. The results of observations of student activities observed an average of 92.4%, The results of observations of student activities asked an average of 85.6%, The results of observations of student activities tried with an average of 84.9%, The results of observations of student activities associated with reasoning an average of 89.4%, the results of observations of student activities communicate with an average of 83.9%. The average score at 69.8 pretest and 82.3 at posttest. This proves that the PPKn module of environmental love material by using the example non example learning model is feasible, easy, and effective for use in class II grade students. This research has implications for the use of the PPKn module on environmental love material by using the example non example learning model to increase student activity and activity